The Impact Implementation Program of Corporate Social Responsibity of PT. Kuansing Inti Makmur Toward Society Development Around Mining Area - Marisa Oktavia; Maulana Yusuf; Ardiyan Saptawan (Sriwijaya Journal of Environment, 2018)
AbstractThis study aims to determine the impact implementation of corporate social responsibility (CSR) program PT. Kuansing Inti Makmur (PT KIM) towards the development of communities around the tambanag area and impact of the program. The company's mission is to build sustainable growth through high standards of occupational safety, development of good community programs and robust environmental management. Corporate social responsibility has become one of the most important issues facing the mining industry. Every mining activity is required to develop and empower the communities surrounding the mining area. This is stated in Permen ESDM No 41 of 2016. Techniques in determining informants are taken by purposive sampling, the community development program consists of four areas: education, health, economics and infrastructure. Data processing research using descriptive qualitative analysis. Based on the results of research can be concluded that the impact implementation of CSR programs on community development in the education is felt by the community is enough to help with the percentage of 60%, the health field is felt by the public is enough to help with the percentage of 60%, the perceived the community's economy has less impact on economic improvement with 51% percentage, infrastructure perceived the community is very helpful with 80% percentage. Keywords: Implementation, Impact of CSR Implementation Abstrak (Indonesian)Tujuan dari penelitian ini  untuk mengetahui dampak implementasi program corporate social responsibility (CSR) pengembangan masyarakat PT. Kuansing Inti Makmur (PT. KIM) terhadap masyarakat sekitar wilayah tambang dan dampak dari program tersebut terhadap masyarakat. Misi PT. KIM bertujuan membangun pertumbuhan berkesinambungan melalui standar keselamatan kerja yang tinggi, pengembangan program kemasyarakatan yang baik dan pengelolaan lingkungan hidup yang tangguh. Tanggung jawab sosial perusahaan   telah menjadi salah satu isu yang  paling penting yang dihadapi industri pertambangan. Setiap kegiatan pertambangan diwajibkan melakukan program pengembangan dan pemberdayaan terhadap masyarakat sekitar wilayah tambang yang telah diatur dalam Permen ESDM No 41 Tahun 2016. Metoda yang digunakan dalam pengambilan  informan yaitu secara purposive sampling, program pengembangan masyarakat terdiri dari empat bidang yaitu bidang pendidikan, kesehatan, ekonomi dan infrastruktur. Pengolahan data penelitian menggunakan analisis deskritif kualitatif. Bedasarkan hasil penelitian dapat disimpulkan dampak implementasi program CSR pengembangan masyarakat dalam bidang pendidikan dirasakan masyarakat  cukup membantu dengan persentase 60%, bidang kesehatan  dirasakan masyarakat cukup membantu dengan persentase 60%, bidang ekonomi dirasakan masyarakat kurang berdampak terhadap peningkatan ekonomi dengan persentase 51%, bidang infrastruktur dirasakan masyarakat sangat membantu dengan persentase  80%.  Kata Kunci: Implementasi program pengembangan, Dampak Implementasi Program CSR